The Association Between Early Menarche and Increased Risk of Cervical Cancer: A Systematic Review - Bangar Parlinggoman Tua; Yahya Nurlianto; Mutia Juliana; Lina Haryani; Nanik Cahyati (The Indonesian Journal of General Medicine, 2025)
Introduction: Cervical cancer (CC) remains a significant global health burden, primarily driven by persistent high-risk human papillomavirus (HPV) infection. While HPV is the necessary cause, the role of host reproductive cofactors, such as early menarche, in promoting carcinogenesis remains controversial. This systematic review synthesizes the epidemiological evidence on the association between early menarcheal age and the risk of cervical cancer and its precursors. Methods: This review was conducted adhering to the PRISMA 2020 guidelines. A systematic search of PubMed, EMBASE, and Web of Science was performed to identify observational (cohort and case-control) studies published to date. Studies assessing the risk of invasive cervical cancer (ICC), cervical intraepithelial neoplasia (CIN/HSIL), or high-risk HPV (HR-HPV) infection in relation to menarcheal age were included. The methodological quality and risk of bias for included non-randomized studies were rigorously assessed using the Risk Of Bias In Non-randomized Studies - of Interventions (ROBINS-I) tool. Results: Seventeen studies met the inclusion criteria. A subset of case-control and cross-sectional studies reported a statistically significant positive association between early menarche and cervical disease. Notably, one meta-analysis of Chinese studies reported a pooled Odds Ratio (OR) of 3.242 for ICC. Another study found a strong association between early menarche (<13 years) and HPV 16/18 infection (OR = 6.2). A 2023 study also identified early menarche as a significant risk factor for high-grade squamous intraepithelial lesions (HSIL). However, these findings are contradicted by larger, more methodologically robust prospective cohort and pooled case-control analyses. These high-quality studies, which included comprehensive adjustment for key confounders, found no significant independent association between menarcheal age and risk of ICC. The evidence demonstrates that the observed association is strongly mediated by age at first sexual intercourse (AFSI), which is significantly predicted by early menarche (e.g., OR = 6.4). Discussion: The data highlights a critical epidemiological challenge in distinguishing between behavioral mediation and biological causation. The findings are evaluated through two primary pathways: 1) The behavioral-mediation pathway, where early menarche serves as a robust proxy for early AFSI and subsequent HPV exposure; and 2) The biological-plausibility pathway, which posits that early endogenous estrogen exposure creates a "window of vulnerability" in the cervical transformation zone, increasing susceptibility to HPV. The robust null findings in studies that control for AFSI, alongside recent data distinguishing risk for uterine (significant) versus cervical (null) cancer, strongly support the behavioral-mediation pathway. Conclusion: While several studies report a significant positive association, the weight of the highest-quality epidemiological evidence suggests that early menarche is not a direct, independent causal factor for cervical cancer. Instead, it functions as a significant indirect risk marker. The association is robustly and almost entirely mediated by the strong correlation between early menarche and early sexual debut. Public health interventions should therefore focus on this behavioral link, targeting education and HPV vaccination to adolescents, particularly those undergoing early pubertal maturation.